2014
DOI: 10.1016/j.pain.2014.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Pain and placebo in pediatrics: A comprehensive review of laboratory and clinical findings

Abstract: Pain modulation by placebo mechanisms is one of the most robust and best-studied phenomena, yet almost all research investigating the mechanisms and implications of the placebo analgesia are based on adult research. After highlighting crucial aspects that need to be considered in studying pain modulation in children, this comprehensive review examines studies related to pain modulation with an emphasis on factors such as age, neural development and pain measures. Psychological mechanisms underlying placebo eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 72 publications
3
18
0
1
Order By: Relevance
“…Evidence from clinical studies suggests that placebo response rates are higher in children compared to adults, supporting anecdotal reports and the common view of higher placebo responses in children 27 . However, placebo response rates in RCTs are also influenced by the natural course of the disease which might be age-dependent.…”
Section: Placebo-responses In Childrensupporting
confidence: 54%
See 1 more Smart Citation
“…Evidence from clinical studies suggests that placebo response rates are higher in children compared to adults, supporting anecdotal reports and the common view of higher placebo responses in children 27 . However, placebo response rates in RCTs are also influenced by the natural course of the disease which might be age-dependent.…”
Section: Placebo-responses In Childrensupporting
confidence: 54%
“…A meta-analysis of placebo-controlled trials for the acute or preventive treatment of migraine revealed stronger placebo analgesic effects in children compared to adults 19 . Similar effects have been reported in epilepsy 23 , attention-deficit disorder 34 and major depression 8 (for recent reviews regarding placebo effects in children see 16,27 ). Clinical improvements observed in the placebo groups of clinical trials, also referred to as placebo effects, can be the result of spontaneous remission, regression to the mean, natural course of a disease, biases and true placebo responses.…”
Section: Introductionmentioning
confidence: 63%
“…Drug actions and placebo effects may interact additively or synergistically in some conditions, such that a treatment is less effective if the placebo component is absent. Therefore, patients’ beliefs and expectancies should be exploited to optimize treatment outcomes (Bingel et al, 2011) in adult as well as pediatric populations (Simmons et al, 2014). …”
Section: Role and Manipulation Of Expectanciesmentioning
confidence: 99%
“…Placebo treatments have known effects on endogenous pharmacology, as well as the cognitive and conditioning systems in humans [312][313][314][315][316][317][318][319]. The placebo response rate is higher in children compared with adults [320,321]. Patient expectations and the doctor-patient relationship contribute to placebo analgesia responses and are unique to the individual [322].…”
Section: The Mechanism and Effects Of Ivlt In Chronic Painmentioning
confidence: 99%